2016
DOI: 10.1021/acsomega.6b00090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nanosecond Pulsed Electric Fields on the Intracellular Function of HeLa Cells As Revealed by NADH Autofluorescence Microscopy

Abstract: The fluorescence lifetime of the endogenous fluorophore of reduced nicotinamide adenine dinucleotide (NADH) in HeLa cells is affected by the application of nanosecond pulsed electric fields (nsPEFs). In this study, we found that after nsPEF application, the fluorescence lifetime became longer and then decreased in a stepwise manner upon further application, irrespective of the pulse width in the range of 10–50 ns. This application time dependence of the NADH fluorescence lifetime is very similar to the time-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…The observed pulse-width dependence of the electric field effect on the intensity and lifetime of NADH fluorescence in these normal and cancer cells is the same as the one observed in HeLa cells, 25 implying that these field effects are common in live cells. In HeLa cells, it was suggested that the so called mitochondrial permeability transition pore complex, which may induce apoptosis, is generated by the application of nsPEF, which has a pulse width as large as 50 ns.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The observed pulse-width dependence of the electric field effect on the intensity and lifetime of NADH fluorescence in these normal and cancer cells is the same as the one observed in HeLa cells, 25 implying that these field effects are common in live cells. In HeLa cells, it was suggested that the so called mitochondrial permeability transition pore complex, which may induce apoptosis, is generated by the application of nsPEF, which has a pulse width as large as 50 ns.…”
Section: Resultssupporting
confidence: 67%
“…In fact, some morphological changes were detected after application of nsPEF in our study in both the cell types, depending on the amplitude and pulse width of the applied electric field, as shown in Figures S5 and S6 . The detection of apoptosis using the fluorescence lifetime of NADH has a great advantage of confirming apoptosis with label-free detection, and this method has been applied in our previous study regarding the nanosecond pulsed field-induced apoptosis of HeLa cells 25 and also in a recent study by another group. 30 …”
Section: Resultsmentioning
confidence: 99%
“…As shown in our previous reports of pulsed electric field effects on autofluorescence lifetime in different cell lines such as HeLa cells, WFB and W31 cells, and MRC‐5 and H661 cells, NADH fluorescence lifetime became longer after application of nanosecond pulsed electric field, that is, the nonradiative decay rate at the emitting state of NADH is decreased by applied electric fields. Therefore, there is also a possibility that the difference in the nonradiative decay rate of NADH and FAD in cancerous and normal cells might be induced by the effects of intracellular electric fields.…”
Section: Resultssupporting
confidence: 61%
“…It has been recognized that NADH participates in the O 2 − generation process, as an electron donor . The short lifetime indicates the large nonradiative decay rate of NADH, which may be mainly attributed to a large electron transfer rate in cancerous cells through the generation of excessive O 2 − , compared to that in normal cells . Along with these reactions, oxidation of NADH increases the concentration of NAD + in cells, which may in turn affect the interaction between the isoalloxazine ring and the adenine ring of FAD .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation